Chilean Validation of the Posttraumatic Stress Disorder Checklist-Civilian Version (Pcl-C) After the Earthquake on February 27 2010 - Vera-Villarroel, P; Celis-Atenas, K (2011)
Posttraumatic stress disorder (PTSD) is an anxiety disorder in which an individual re-experiences a traumatic event, avoids situations related to it, and shows excessive arousal. The disorder appears after experiencing a lifethreatening event, such as a war or a natural disaster. Thus, the validation of tests which assess the disorder after the earthquake on February 27, 2010, in Chile is crucial for its evaluation and subsequent intervention. The present study includes psychometric data for the Posttraumatic Stress Disorder Checklist-Civilian version (PCL-C) on a sample of 509 survivors of the disaster. Values indicate good psychometric properties of the questionnaire. © Psychological Reports 2011.